2007
DOI: 10.1016/j.abb.2007.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial P450-dependent arachidonic acid metabolism by TCDD-induced hepatic CYP1A5; conversion of EETs to DHETs by mitochondrial soluble epoxide hydrolase

Abstract: Several P450 enzymes localized in the endoplasmic reticulum and thought to be involved primarily in xenobiotic metabolism, including mouse and rat CYP1A1 and mouse CYP1A2, have also been found to translocate to mitochondria. We report here that the environmental toxin 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) induces enzymatically active CYP1A4/1A5, the avian orthologs of mammalian CYP1A1/1A2, in chick embryo liver mitochondria as well as in microsomes. P450 proteins and activity levels (CYP1A4-dependent 7-et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 64 publications
2
4
0
Order By: Relevance
“…CYP4A and GPR75 was co-expressed with NeuN inside both granular and pyramidal neuron populations in all 6 layers of the neocortex as well as granular and pyramidal neurons of the hippocampus (Figures 6A-C, Figures 3A-F). The intercellular expression pattern of CYP4A was circumferential to the nucleus ( Figure 6B) consistent with the location of CYP4A inside the endoplasmic reticulum (51). CYP4A expression in neurons of the hippocampus (CA1-CA3) vs. the somatosensory barrel cortex was quantified in Figures 7A-E. A significantly lower (P < 0.0001) population of CYP4A positive neurons in the hippocampus (1.45) vs. neocortex (6.10) per measurement field was observed ( Figure 7D).…”
Section: Expression Of Cyp4a and Gpr75 In Neurons And Astrocytessupporting
confidence: 78%
See 1 more Smart Citation
“…CYP4A and GPR75 was co-expressed with NeuN inside both granular and pyramidal neuron populations in all 6 layers of the neocortex as well as granular and pyramidal neurons of the hippocampus (Figures 6A-C, Figures 3A-F). The intercellular expression pattern of CYP4A was circumferential to the nucleus ( Figure 6B) consistent with the location of CYP4A inside the endoplasmic reticulum (51). CYP4A expression in neurons of the hippocampus (CA1-CA3) vs. the somatosensory barrel cortex was quantified in Figures 7A-E. A significantly lower (P < 0.0001) population of CYP4A positive neurons in the hippocampus (1.45) vs. neocortex (6.10) per measurement field was observed ( Figure 7D).…”
Section: Expression Of Cyp4a and Gpr75 In Neurons And Astrocytessupporting
confidence: 78%
“…CYP4A was co-expressed in GFAP positive astrocyte cell bodies in the neocortex and hippocampus ( Figures 8A,B, 9A-I). The expression of CYP4A inside the cell body of the astrocyte was also found to be circumferential to the nucleus as expected inside the endoplasmic reticulum (51). Most interestingly, the co-expression of CYP4A in astrocytes was not apparent in the vast majority of astrocytes but rather in minor subpopulations ( Figure 8A).…”
Section: Expression Of Cyp4a and Gpr75 In Neurons And Astrocytessupporting
confidence: 63%
“…While roles of CYPs in cancer cell respiration are unknown, the discovery of CYP enzymes and sEH in mitochondria (Addya et al, 1997; Labitzke et al, 2007) suggested a new site of CYP activity, but whether and how these observations may be relevant to mitochondrial function was unclear. More recently, EETs have been implicated in the mitochondrial function of cardiac myocytes (Katragadda et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Citrate and fumarate are important intermediates for the TCA cycle, which is crucial for energy metabolism. Previous studies indicated TCDD-induced hepatotoxicity was initiated by an inhibition of mitochondrial respiratory function, 28 which inevitably led to changes in the TCA cycle intermediates in the liver and serum profiles. This can also be confirmed by significant depletion of acetyl-CoA level, which is regarded as the “Hub of Metabolism” 29 and is involved in many biochemical reactions, in the liver of TCDF-treated mice.…”
Section: Discussionmentioning
confidence: 99%